Pengaruh Penggunaan Polivinil Pirolidon (Pvp) Sebagai Bahan Pengikat Terhadap Sifat Fisik Dalam Formulasi Sediaan Granul Effervescent Ekstrak Buah Asam Gelugur (Garcinia atroviridis Griff. Et Anders.). - Sala, Yameela, Suprapto, M.Sc., Apt (2016)
Gelugur extract (Garcinia atroviridis Griff. Et Anders.). Show that it promotes weight loss and may also reduce appetite gelugur ekstrak maybe particularly effective when higher amounts of carbohydrates are eaten, as Hydrocitic acid (HCA) appeans to divere carbohydrates away from being converted in fat and instead favor formation of glycogen. Effervescent granules were chosen as the alternative of dosage form because effercescent granul gave the fresh sensation comfortable easy to use and preparation of liguid with accurate dosage could be done as soon as possible. Binder is the important component for making the effervescent granules. It compacted together. Binder is used in this practice namely polyvinyl pyrrolidone (PVP). This study aims to determine the effect of variations in the levels of PVP as a binder to the physical properties of gelugur ekstrak effervescent granules. Gelugur extracts, extracted is maceration method with ethanol 96% and effervescent granules. The granulation method is made by wet the effervescent granule. There are 3 formula to make effervescent granul. Eace formula is the difference PVP concentration suce as: formulation that I (1%) formulations II (3%) and formulations III (5%). The effervescent granul evaluetion include tested are flow rate and angel of repose then tes physical. These physical properties tests were used to get know the guality of granules formula produced. Data is analyzed on the theoretical approaches and statistical analysis of (Anova) one way with a 95% confidence rate. The results of this research showed that effervescent granules which were produced had fulfiled the test reguirement of flow rate and angel of repose. PVP had a dominant effect towart the entire physical propeties of effervescent granules. The result of practice physical properties showed that the best formular is formula I for containing PVP (1%).